Case Report: Kombinasi Hidroterapi Dan Serai Untuk Menurunkan Nyeri Pada Lansia - Aviani, Agista Wulan; Lestari , Nina Dwi (Universitas Muhammadiyah Yogyakarta, 2023)
Background – Joint pain is a serious problem experienced by some of the elderly which can interfere with the psychology of the elderly, such as depression, dementia, social isolation to greater functional impairment Pain is often felt by the elderly but pain is not part of aging. Non-pharmacological pain management efforts are urgently needed to reduce complaints of pain experienced by the elderly, one of which is by using a combination of hydrotherapy and lemongrass. Objective – This case study aims to analyze the implementation of independent nursing in the form of a combination of hydrotherapy and lemongrass in reducing pain levels in the elderly. Method – The method used is a case study on an elderly with complaints of chronic joint pain in the lower extremities. The instrument used is a numerical rating scale to measure the level of pain before and after therapy. The intervention was carried out for seven days routinely in the morning and evening. Results – Non-pharmacological interventions through a combination of hydrotherapy and lemon grass can reduce pain levels in the elderly from a scale of seven to five. Suggestion – Elderly who experience pain can take advantage of a combination of hydrotherapy and lemon grass to reduce pain in their bodies. Keywords: Pain, Elderly, Hydrotherapy, Lemongrass